2018
DOI: 10.1002/anie.201809035
|View full text |Cite
|
Sign up to set email alerts
|

Sigmatropic Dearomatization/Defluorination Strategy for C−F Transformation: Synthesis of Fluorinated Benzofurans from Polyfluorophenols

Abstract: Facile synthesis of fluorinated benzofurans from polyfluorophenols has been accomplished by means of a sigmatropic dearomatization/defluorination strategy composed of three processes: (1) interrupted Pummerer reaction of ketene dithioacetal monoxides with polyfluorophenols followed by [3,3] sigmatropic rearrangement, (2) Zn-mediated smooth reductive removal of fluoride from the dearomatized intermediate, and (3) acid-promoted cyclization/aromatization. Mechanistic investigations revealed important characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Recently,w eh ave demonstrated as igmatropic dearomatization/defluorination sequence as an ew strategy for selective CÀFt ransformations of polyfluorophenols for annulative synthesiso ff luorinated benzofurans (Scheme 1a). [9,10] In the presence of trifluoroacetica nhydride (TFAA), polyfluorophenols undergoi nterrupted Pummererr eaction [11] with ketene dithioacetal monoxide (KDM) to form SÀO-tethered sulfonium A.T hen, CÀCb ond-forming charge-accelerated [3,3] sigmatropic rearrangemento ccurs with dearomatization of the phenol ring to give dearomatized intermediate B. [12] Subsequent addition of Zn induces reductive defluorination to form phenol C.A ssisted by rearomatization, the reductive defluorinationp roceeds with the moderate reducing agent underm ild reaction conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently,w eh ave demonstrated as igmatropic dearomatization/defluorination sequence as an ew strategy for selective CÀFt ransformations of polyfluorophenols for annulative synthesiso ff luorinated benzofurans (Scheme 1a). [9,10] In the presence of trifluoroacetica nhydride (TFAA), polyfluorophenols undergoi nterrupted Pummererr eaction [11] with ketene dithioacetal monoxide (KDM) to form SÀO-tethered sulfonium A.T hen, CÀCb ond-forming charge-accelerated [3,3] sigmatropic rearrangemento ccurs with dearomatization of the phenol ring to give dearomatized intermediate B. [12] Subsequent addition of Zn induces reductive defluorination to form phenol C.A ssisted by rearomatization, the reductive defluorinationp roceeds with the moderate reducing agent underm ild reaction conditions.…”
mentioning
confidence: 99%
“…With benzothienyls ulfoxide 1a and 2,6-difluorophenol (2a) as models ubstrates, we optimized the reactionc onditions based on our previous defluorinative transformation. [9] Optimization study revealed that TFAA (2.0equiv) and Zn powder (5.0 equiv) were found to be optimal as an activatora nd as a reductant,r espectively. [13] Moreover,a na ddition of as mall amount of trifluoroacetic acid (TFA) wasc rucial for the reproducibility of the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, they accomplished a facile synthesis of fluorinated benzofurans from polyfluorophenols by means of a sigmatropic dearomatization/defluorination strategy composed of three processes: (1) interrupted Pummerer reaction of ketene dithioacetal monoxides, activated by TFFA, with polyfluorophenols followed by [3,3] sigmatropic rearrangement; (2) Zn-mediated smooth reductive removal of fluoride from the dearomatized intermediate; and (3) acid-promoted cyclization/aromatization to lead to benzofuran in 90% overall yield. Some of the fluorinated benzofurans were transformed by utilizing the 2-methylsulfanyl moieties [179] (Scheme 54). Procter's group reported a transition-metal-free synthesis of benzofurans from benzothiophenes and phenols which exploited the unique reactivity of sulfoxides [180].…”
Section: Via Interrupted Pummerer Reaction/[33] Sigmatropic Rearrangement/cyclizationmentioning
confidence: 99%
“…(1) interrupted Pummerer reaction of ketene dithioacetal monoxides, activated by TFFA, with polyfluorophenols followed by [3,3] sigmatropic rearrangement; (2) Zn-mediated smooth reductive removal of fluoride from the dearomatized intermediate; and (3) acid-promoted cyclization/aromatization to lead to benzofuran in 90% overall yield. Some of the fluorinated benzofurans were transformed by utilizing the 2-methylsulfanyl moieties [179] (Scheme 54). Palladium-catalyzed oxidative annulations between phenols and alkenylcarboxylic acids produced a library of benzofuran compounds.…”
Section: Via Interrupted Pummerer Reaction/[33] Sigmatropic Rearrangement/cyclizationmentioning
confidence: 99%